Bridging studies for nurses and midwives in Poland – Implementation of the Directive 2005/36/EC – Assumptions and results - Cholewka, Beata; Zinkowska, Dorota; Wrońska, Irena (Nursing in the 21st Century, 2013)
BRIDGING STUDIES FOR NURSES AND MIDWIVES IN POLAND – IMPLEMENTATION OF THE DIRECTIVE 2005/36/EC – ASSUMPTIONS AND RESULTSThis paper presents bridging training for nurses and midwives in relation to the Bologna Process, shows results of the training, required under the Directive 2005/36/EC as a condition for the automatic recognition of the qualifications of Polish nurses and midwives in the European Union, and its impact on the professional mobility of nurses and midwives. This article mentions also, in relation to the currently ongoing work on the modernization of the Directive, change of the rules of the recognition of professional qualifications of Polish nurses by the Member States of the European Union, postulated by the Polish Government.This work also presents, in chronological way, projects, thanks to which, nurses and midwives with secondary medical education have been able to continue benefiting from EU funds for education on bridging studies after accession of Poland to the EU. Particular attention has been paid to the project, run in the current financial perspective 2007-2013, co-financed by the European Social Fund under the Human Capital Operational Programme, which solves, in systemic way for almost 34 thousand nurses and midwives, the problem of an automatic recognition of professional qualifications.